The anatomical basis of third-degree atrioventricular block in dogs with atrioventricular valve endocardiosis. (February 2023) - Machida, Noboru; Sasaki, Takafumi; Kimura, Yusuke; Hirakawa, Atsushi
Abstract: The cardiac conduction system was examined histologically in 13 canine cases of atrioventricular (AV) valve endocardiosis with third-degree AV block. In all cases, gross examination revealed marked thickening and distortion of the base of the central fibrous body (CFB) and varying degrees of endocardial thickening of the upper portion of the ventricular septum (VS) as well as marked thickening of the mitral and tricuspid valve leaflets due to myxomatous degeneration. Microscopically, the thickened and distorted CFB had encased or trapped, either partly or totally, the underlying penetrating and branching portions of the AV bundle. The myxomatous and/or fibrofatty tissue, which had proliferated at the base of the extensive CFB, protruded into or encroached on the AV bundle, causing severe (51–75%) to very severe (76% or more) reduction of the conduction fibres. The upper portions of the left and right bundle branches were involved in the endocardial thickening due to degenerative and fibrotic changes at the uppermost VS; however, both bundle branches were much less severely affected than the AV bundle, the degree of reduction of the conduction fibres ranging from mild (25% or less) to moderate (26–50%). These observations suggest that the sites most vulnerable to lesions in the AV conduction system are the penetrating and branching portions of the AV bundle, which would represent the anatomical basis for third-degree AV block in canine cases of AV valve endocardiosis.